Taxonomy and zoogeography of the mesozoic cytherurid ostracoda from West-Central Argentina - Ballent, Sara Cristina (2009)
The status of thirty four species of the cytheroidean ostracod family Cytheruridae from the Neuquén Basin, west-central Argentina is reviewed. These species belong to the following nine genera: Eucytherura Müller, ranging in this study from Pliensbachian to Valanginian and represented by fourteen species; Kangarina Coryell and Fields, Aalenian-Bajocian, with a single species; Acrocythere Neale, Hauterivian, one species; Paranotacythere Bassiouni, Berriasian, two species; Procytherura Whatley, Pliensbachian to Hauterivian, twelve species; Cytheropteron Sars, Aalenian-Bajocian, one species: Eocytheropteron Alexander, Hauterivian, one species; Paradoxorhyncha Chapman, Aalenian-Bajocian, one species; and Paracytheridea Müller, Berriasian, one species. Of the three subfamilies of the Cytheruridae, the Cytherurinae, with thirty species are by far the most numerous and abundant throughout the study. The other two subfamilies, the Cytheropterinae are represented by three species and the Paracytherideinae by a single species of the nominative genus. Several of the species are very widely distributed geographically and have, for example, also been recorded from Europe; others indicate close links with South Africa and Australia. The stratigraphical ranges of certain genera have been extended as a result of this study. For example, Kangarina has not previously been recorded below the Cretaceous. The Cytheruridae are clearly the most diverse cytheroidean ostracodes in the Mesozoic of the Neuquén Basin and are more diverse than all other groups of ostracodes combined. Four new species, Eucytherura tessae, Eucytherura yunga, Procytherura amygdala and Eocytheropteron immodicus are described. Eucytherura guillaumeae nom. nov. for Eucytherura tuberculata Brenner and Oertli and Eucytherura paranuda nom. nov. for Eucytherura nuda (Brand) are proposed.